α-Lys424 Participates in Insertion of FeMoco to MoFe Protein and Maintains Nitrogenase Activity in Klebsiella oxytoca M5al - Song, Lina; Liu, Pengxi; Jiang, Wei; Guo, Qingjuan; Zhang, Chunxi; Basit, Abdul; Li, Ying; Li, Jilun (Frontiers in Microbiology, 2019)
Our previous investigation of substrates reduction catalyzed by nitrogenase suggested that α-Ile423 of MoFe protein possibly functions as an electron transfer gate to Mo site of active center-"FeMoco". Amino acid residue α-Lys424 connects directly to α-Ile423, and they are located in the same α-helix (α423-431). In the present study, function of α-Lys424 was investigated by replacing it with Arg (alkaline, like Lys), Gln (neutral), Glu (acidic) and Ala (neutral) through site-directed mutagenesis and homologous recombination. The mutants were respectively termed 424R, 424Q, 424E, and 424A. Studies of diazotrophic cell growth, cytological and enzymatic properties indicated that none of the substitutions altered secondary structure of MoFe protein, or normal expression of nifA, nifL and nifD. Substitution of alkaline amino acid (i.e., 424R) maintained acetylene (C2H2) and proton (H+) reduction activities at normal levels similar to that of wild-type, because of its FeMoco content did not reduce. In contrast, substitution of acidic or neutral amino acid (i.e., 424Q, 424E, 424A) impaired the catalytic activity of nitrogenase to varying degrees. Combination of MoFe protein structural simulation and results of a series of experiments, the function of α-Lys424 in ensuring insertion of FeMoco to MoFe protein was further confirmed, and the contribution of α-Lys424 to maintaining low potential of the microenvironment to efficient catalytic activity of nitrogenase was demonstrated.